Indicadores de conexão informacional na Comunidade Fluvial Rolim de Moura do Guaporé – Rondônia - Aldenilson Costa; Fernanda Santos Estrada; Maria Aguiar Pacheco; Nubia Caramello (Confins)
The article investigates the use of information and communication technologies in Rolim de Moura do Guaporé community, a fluvial island of difficult access located more than 800 km from the capital of Rondônia, Porto Velho. The challenge of this research is to understand how the inhabitants of this island can use the digital technologies produced in a globalized way, which intend to reduce the barriers of physical access, opening doors for the inclusion in the world of technology. The research was carried out through a structured interview with the local residents by the application of a questionnaire with 18 questions. The group of researchers was surprised by the percentage of respondents who use radio, television as a source of information and cell phones as a source of communication to work, study, communicate among others, understanding that digital inclusion can break some geographical barriers and make any city inserted in the resources that globalization offers, in the case of the traditional community under analysis the technological instrument that opens the door to the external territorial dimension is the use of cell phones. It was also possible to identify the technological dependence of the wifi signal providers, which OI operator enters via the telephone line and this has internet access that is commercialized locally.